Powering Up Developing Countries through Integration? - Auriol, Emmanuelle; Biancini, Sara (World Bank, Washington, DC, 2013)
Power market integration is analyzed in a two-country model with nationally regulated firms and costly public funds. If the generation costs between the two countries are too similar, negative business stealing outweighs efficiency gains so that the subsequent integration welfare decreases in both regions. Integration is welfare enhancing when the cost difference between two regions is large enough. The benefits from export profits increase the total welfare in the exporting country, whereas the importing country benefits from lower prices. In this case, market integration also improves incentives to invest compared to autarky. The investment levels remain inefficient, however, especially for transportation facilities. Free riding reduces incentives to invest in these public-good components of the network, whereas business stealing tends to decrease the capacity to finance new investment.